Hidup dalam Kesenjangan: Paradox Migran Baru Asal Tiongkok (Xinyimin) dengan Masyarakat di Indonesia - Paulus Rudolf Yuniarto (Jurnal Identitas, 2024)
New migrants from China (Xinyimin) in Indonesia generally migrate for employment, business opportunities, educational advancement, and marriage. Their presence fosters socio-cultural exchange and offers a significant perspective on the interaction between Indonesians and Xinyimin. However, the ongoing influx of migrants from China since the country’s economic boom has led to an expanding gap between them and the local population. This disparity is perceived as a threat to the livelihoods of Indonesians and the established social order. Consequently, the host-immigrant tensions have sparked local-national political debates. The friction between Chinese workers and local Indonesians has garnered public attention, with local workers expressing resentment toward the higher wages of Chinese migrants while struggling to secure comparable earnings, regardless of nationality. The presence of Xinyimin in Indonesia is viewed not only as a foreign element but also as a competitive force, raising concerns due to their perceived exploitation of local resources. This situation presents a significant obstacle to the interaction and acculturation of Xinyimin in Indonesia.